Mathematical modelling in textbook tasks and national examination in Norwegian upper secondary school - Berget, Ingeborg Katrin Lid (NOMAD Nordic Studies in Mathematics Education, 2022)
Modelling competence is defined as the ability to carry through all steps of a mathematical modelling process, to solve a non-mathematical problem by mathematics. In this study, Norwegian textbook modelling tasks and tasks from the national exam are analyzed through the lens of a modelling cycle. The findings discussed as the enacted curriculum (textbook tasks) and assessed curriculum (exam tasks) are seen in relation to the intended curriculum. The results show different starting points of the modelling process in the intended curriculum and the tasks from textbooks and exam. The findings indicate different perspectives on mathematical modelling in the curriculum (modelling for developing modelling competence) and the textbook tasks and the national exam, where only parts of the modelling process are included.